The effectiveness of non‐pharmacological interventions on cancer related fatigue in breast cancer patients: A protocol for systematic review and network meta‐analysis - Yu Liu; Pengzhu Xu; Chunli Song; Tongtong Jiang; Jun‐E Liu; Tieying Shi (Wiley, 2022)
Abstract Aim To assess the effect of different non‐pharmacological interventions on cancer‐related fatigue (CRF) in breast cancer (BC) patients and identify the most effective method for improving CRF. Design A systematic review and network meta‐analysis. Methods Literature will be searched in the ongoing trail in the Clinical Trials.gov, World Health Organization, the International Clinical Trials Registry Platform, Cochrane Library, PubMed, EMBASE, Web of Science and CINAHL, from the inception until December 31, 2020. Two independent researchers will rigorously screen the literature according to the inclusion and exclusion criteria and assess the risk of bias based on the Cochrane Collaboration's Tool of RCTs. Stata 13.0 and Aggregate Data Drug Information System will be used for data analysis. Results This protocol has been registered on the PROSPERO website (registration number is CRD42020222093). This study will provide the reliable evidence of the most effective non‐pharmacological intervention to improving CRF.